(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The constitution of India guarantees complete freedom and protection to every individual for the fullest realization of his individual personality. In the present age of technical development the problems of labourers are becoming more and more complex. In the light of this thinking a study of welfare programmes for labourers assumes great significance. The objective of the present study is to spell out the need, objective, evolution and to find out the measures for the effective implementation of various labour welfare schemes.